(2-3i)(4+6i) = 8 + 12i - 12i - 18i^2
= 8 + 18
26
2006-11-12 07:13:06
·
answer #1
·
answered by Anonymous
·
1⤊
1⤋
(2-3i)(4 + 6i) = 2(2-3i)(2+3i) = 2(4+9) = 26.
2006-11-12 07:15:22
·
answer #2
·
answered by steiner1745 7
·
0⤊
0⤋
Combine 6i and -3i and you get 3i. then combine the 4 and t to get 6. rewrite the equation 3i+6 thats your answer!!!!!
2006-11-12 07:19:39
·
answer #3
·
answered by che-che 2
·
0⤊
0⤋
36x^2 - 65x - 36 When all else fails, apply the quadratic formula and work back from there x = (65 +/- sqrt(65^2 - 4 * 36 * (-36)) / (2 * 36) x = (65 +/- sqrt(65^2 + 72^2)) / 72 x = (65 +/- sqrt(97^2)) / 72 x = (65 +/- 97) / 72 x = 162/72 , -32/72 x = 81/36 , -4/9 x = 9/4 , -4/9 (4x - 9) * (9x + 4) 9s^2 - 6st + t^2 (3s - t)^2 3 * (x^2 + 4)^4 * 2x * (x - 3)^4 + (x^2 + 4)^5 * (x - 3)^3 => (x^2 + 4)^4 * (x - 3)^3 * (3 * 2x * (x - 3) + (x^2 + 4)) => (x^2 + 4)^4 * (x - 3)^3 * (6x * (x - 3) + x^2 + 4) => (x^2 + 4)^4 * (x - 3)^3 * (6x^2 - 18x + x^2 + 4) => (x^2 + 4)^4 * (x - 3)^3 * (7x^2 - 18x + 4)
2016-03-28 03:25:44
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
=8+12i-12i-18 i^2
=8+18
=26
2006-11-12 07:31:29
·
answer #5
·
answered by openpsychy 6
·
0⤊
0⤋
not much different that multiplying binomials. The only difference is that i^2=-1.
Use the FOIL rule to remember how to do it: http://en.wikipedia.org/wiki/FOIL_rule
2006-11-12 07:13:34
·
answer #6
·
answered by arbiter007 6
·
0⤊
0⤋
-18i^2 + 8
2006-11-12 07:13:28
·
answer #7
·
answered by jacinablackbox 4
·
0⤊
2⤋